2022
DOI: 10.3390/jcm11041140
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Severity and Health-Related Quality of Life in Patients with Atrial Fibrillation: Findings from the Observational ARENA Study

Abstract: Background: Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia and is associated with impaired health-related quality of life (HRQoL), high symptom severity, and poor cardiovascular outcomes. Both clinical and psychological factors may contribute to symptom severity and HRQoL in AF. Methods: Using data from the observational Atrial Fibrillation Rhine-Neckar Region (ARENA) trial, we identified medical and psychosocial factors associated with AF-related symptom severity using European Heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…It is not just the case that those who have more recently experienced symptoms are more stressed, but instead, stress in itself adds additional variance explained over and above recency of symptoms. Although prior studies have reported that patients perceive that stress triggers/causes their AF symptom episodes [ 10 13 ] or increases symptom severity [ 33 ] this is the first study to link perceived stress as a unique contributor to HRQoL in the AF population. Further, it expands on other evidence showing the impact of psychological distress, namely depression and/or anxiety on greater AF symptom severity, diminished HRQoL, and recurrence of AF [ 34 ] and draws attention to the need to address patients perceived stress in addition to symptom control in enhancing patients HRQoL and AF management [ 35 ].…”
Section: Discussionmentioning
confidence: 98%
“…It is not just the case that those who have more recently experienced symptoms are more stressed, but instead, stress in itself adds additional variance explained over and above recency of symptoms. Although prior studies have reported that patients perceive that stress triggers/causes their AF symptom episodes [ 10 13 ] or increases symptom severity [ 33 ] this is the first study to link perceived stress as a unique contributor to HRQoL in the AF population. Further, it expands on other evidence showing the impact of psychological distress, namely depression and/or anxiety on greater AF symptom severity, diminished HRQoL, and recurrence of AF [ 34 ] and draws attention to the need to address patients perceived stress in addition to symptom control in enhancing patients HRQoL and AF management [ 35 ].…”
Section: Discussionmentioning
confidence: 98%
“… 32 By contrast, in 1218 new-onset AF patients from the ARENA (Atrial Fibrillation RhineNeckar Region) trial, symptom severity was not associated with differences in HRQOL. 33 …”
Section: Discussionmentioning
confidence: 99%
“…In the ARENA trial, history of coronary artery disease was associated with 0.056 reduction in HRQOL [(95% CI −0.089, −0.023), P = 0.001], whereas a history of stroke/TIA had modest non-significant associations [estimate of −0.039 (95% CI −0.081, 0.003); P = 0.068]. 33 By contrast, data from the Euro heart survey reported stroke as having the largest decrement in HRQOL [−0.272 (95% CI −0.345, −0.198)]. 34 However, both the ARENA trial and the Euro Heart Survey analyses were cross-sectional and the latter study enrolled participants between 2003 and 2004, prior to the introduction of novel oral anticoagulation therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients with AF often experience cardiac-specific symptoms, such as palpitations and chest pain, and nonspecific symptoms, such as fatigue, dyspnea, and dizziness. These symptom burdens can lead to poor prognoses, such as depression 40 and decreased quality of life 41 . Studies indicated that AF episodes present with near syncope and, in some cases, even fainting, can limit patients' daily life and physical activities 42,43 .…”
Section: Discussionmentioning
confidence: 99%